An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

The position of assets vested in a sham trust - Diedericks, C. A. (North-West University, 2018)
The concept of a sham trust has changed over the years. Presently it is defined as a perceived entity that is not entirely what it portrays to be. In addition, a sham is therefore regarded as invalid with a deceiving nature. A sham trust has the consequence that all the benefits and protection of assets are destroyed, seeing that no trust actually came into existence. Considering the above, for the purpose of the present study, only an inter vivos trust was evaluated and discussed in detail. The law of contract is considered to be the foundation of the principles for an inter vivos trust. Therefore, the law of contracts can be applied to solve problems presented by trusts. During the course of the present research, it became evident: in instances where a trust is declared a sham, the consequence is that the trust will be deemed void. There are instances where a sale agreement has been concluded prior to the discovery of the true nature of the trust, namely it being a sham. This raises the question on the legal position of assets vested in a sham trust. A further question arises about the consequences and whether the courts should set a guideline for such instances. From the findings it is evident that such a guideline is necessary. This would enable courts to determine the consequences of assets vested in a sham trust. There are various possibilities regarding consequences for assets vested in a sham trust. To determine the applicable consequence, the court should deal with each case individually based on the facts of that particular circumstances. This consequence could either entail that the assets should fall within the founder’s personal estate, or whether the concluded sale agreement should be deemed void. It is evident that the courts struggled with the distinction between a sham and alter ego trust, however, the case law referred to below gives more clarity in this regard. A proper formulation of the aspects of sham and alter ego trusts was provided in the cases of Van Zyl v Kaye1 and Van der Merwe v Hydraulics.2 The formulation of the two aspects in the above-mentioned cases was confirmed in the Supreme Court of Appeal judgement in the case of WT v KT.3 In the Khabola v Ralitabo,4 the court dealt with the typical example of the sham trust. In brief, the fact of the case were, that the parties had the intention to establish a partnership that was simulated to be a trust.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31321
Keywords: Assets; Contract of sale; Intention; Law of contract; Legal position; Sham trust; Snook test; inter vivos trust

The Organisation for the Harmonisation of Business Law in Africa (OHADA) System: Overview of some Benefits and Problem Areas - Leno, Ngaundje Doris (International Journal of Advanced Research and Publications, 2018)
As much as the Organisation for the Harmonisation of Business Law in Africa (OHADA) aims to improve the legal environment for business, the harmonisation process should be seen as a tool of economic integration with several advantages. Despite the achievements and benefits, OHADA, like other regional integration efforts in Africa, has some temporary drawbacks that may become permanent if no effort is made to overcome them. The primary focus of the paper is to present OHADA‟s background; offer an overview of some of the salient benefits of OHADA‟s institutional and regulatory framework; consider OHADA‟s problem areas; and propose possible solutions to the problems. The value of the paper, therefore, lies in the insight it offers into OHADA, the benefits and problems of its institutional and regulatory framework. It is also important because it is laying the foundation in making the OHADA structure available for all Africans.
Keywords: Business law; Harmonisation; OHADA

Modifying contract law principles to accommodate automated transactions in South Africa - Ramokanate, L. L. (North-West University, 2018)
Modern electronic commerce is chiefly characterised by the use of unattended computers in the negotiation and conclusion of agreements. Commonly referred to as "electronic agents," these computers assist their users to negotiate better and profitable deals in virtual marketplaces. In South Africa, the legal force and effect of automated transactions, i.e. agreements concluded by electronic agents, is addressed in section 20 of the Electronic Communications and Transactions Act 25 of 2002 (hereinafter referred to as the ECT Act). According to section 20 (a) of the ECT Act, a valid and enforceable agreement will be formed where an electronic agent performs an action required by law for agreement formation. The same statute provides further in section 20 (b) that a valid and enforceable agreement will be formed where all the parties to a transaction or either one of them uses an electronic agent. The overall effect of these provisions is that an agreement cannot be denied legal validity and enforceability on the ground that an electronic agent was used, whether by one or both parties, to conclude it. Likewise, an agreement cannot be denied legal validity and enforceability on the ground that no human being took part in its formation. Although the ECT Act provides as a general matter that automated transactions are valid and enforceable in South Africa, that statute does not, however, create new rules for the formation of such agreements. This is made clear in section 3, which provides, amongst others, that the ECT Act should not be interpreted to exclude the application of the common law of contract to electronic transactions. Therefore, as with traditional or non-automated agreements, automated transactions too must satisfy the individual requirements of a valid contract at common law. As a matter of fact, the common law theory of contract formation is predominantly based on the assumption that human volition will always play a pivotal role in the making, acceptance or rejection of offers. For that reason, this research proceeds on a strong hypothesis that common law rules and principles pertaining to the formation of agreements are either insufficient or inadequate to accommodate the validity of agreements concluded by computers without the immediate intervention of their users. Consequently, the aim of this research is to discuss how the rules and principles of the common law of contract can be modified or developed in order to accommodate, within the common law theory of contract formation, the statutory validity of automated transactions in South Africa. The discussion of this research is limited to five legal issues, namely the basis of contractual liability in automated transactions, the analysis of offer and acceptance in automated transactions, the time and place of contract formation in automated transactions, the incorporation of standard terms and conditions in automated transactions, and the treatment of mistakes and errors in automated transactions. These issues are discussed first with reference to South African law, primarily with the purpose of determining the extent to which relevant common law rules and principles provide adequate solutions to specific challenges posed by automated transactions. To the extent that relevant common law rules and principles do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this research for their development or modification. As shall be demonstrated in the course of this work, in relation to some of the abovementioned legal issues, the development or modification of common law rules has been done by the ECT Act. These "statutory developments or modifications of the common law" are also discussed in this work, primarily with the aim of determining the extent to which they provide adequate solutions to specific challenges posed by automated transactions. To the extent that these statutory modifications of the common law do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this work on how the relevant provisions of the ECT Act may be interpreted by courts of law or amended by Parliament in order to strengthen the response of that statute. The abovementioned legal issues are also discussed in this work with reference to US and UK law, primarily with the purpose of determining how the law addresses the challenges of automated transactions in these jurisdictions, and to draw valuable lessons for the development or modification of South African contract law.
Keywords: Automated transactions; Autonomous electronic agents; Contract formation; Contract law; Passive electronic agents

What Do Trade Agreements Really Do? - Rodrik, Dani (The Journal of Economic Perspectives, 2018)